2016
DOI: 10.12659/msm.896916
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Apoptosis of Human Umbilical Vein Endothelial Cells was Inhibited by Blueberry Anthocyanin Through Bax- and Caspase 3-Dependent Pathways

Abstract: BackgroundThis study aimed to investigate the inhibitory effect of blueberry anthocyanin (BBA) on Angiotensin II (Ang II)-induced apoptosis of human umbilical vein endothelial cells (HUVECs), and its regulation mechanisms involving Bax and Caspase 3.Material/MethodsHUVECs were first treated by different concentrations of Ang II (10−9, 10−8, 10−7, 10−6, 10−5, and 10−4 mol/L) and BBA (80, 40, 20, 10, 5, and 2.5 μg/ml). After 24 h and 48 h of treatment, MTT was performed to detect the viability of HUVECs. Then, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…HUVEC viability was measured with alamarBlue ( Sarig et al, 2018 ; Krishnamoorthi et al, 2020 ) and the viability trend we observed in our work is comparable to the endothelial viability studied with the presence of TGF-β1, L-NAME, and Ang II as shown by others ( Hirai and Kaji, 1992 ; Mocellin et al, 2004 ; Du et al, 2016 ; Zhang et al, 2020 ). While reversibility of markers of EndoMT in endothelial cells has been reported previously, this reversibility has not been previously characterized as a functional reversal.…”
Section: Discussionsupporting
confidence: 89%
“…HUVEC viability was measured with alamarBlue ( Sarig et al, 2018 ; Krishnamoorthi et al, 2020 ) and the viability trend we observed in our work is comparable to the endothelial viability studied with the presence of TGF-β1, L-NAME, and Ang II as shown by others ( Hirai and Kaji, 1992 ; Mocellin et al, 2004 ; Du et al, 2016 ; Zhang et al, 2020 ). While reversibility of markers of EndoMT in endothelial cells has been reported previously, this reversibility has not been previously characterized as a functional reversal.…”
Section: Discussionsupporting
confidence: 89%
“…activated Bax can induce the release of pro-apoptotic factors and cytochrome c (55). caspase-3 is a member of the cysteine-aspartic acid protease family and plays a central role in cell apoptosis (56,57). The results of the present study indicated that ccnd1 promoted the expression of Ki67 and Bcl-2, and inhibited Bax and cleaved caspase-3, while mir-628-5p partially reversed the effect of ccnd1 on these genes.…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 50%
“…The effect of Ang II on the function of vascular endothelial cells has attracted increasing attention from cardiologists. Previous studies have shown that Ang II can promote cellular functions by stimulating reactive oxygen species production, promoting thrombosis (14), inhibiting nitric oxide production, and promoting vascular endothelial cell apoptosis (15). Our previous studies also showed that Ang II can affect the normal function of endothelial cells by inhibiting nitric oxide synthase or inducing inflammatory reactions in cells (12,16).…”
Section: Discussionmentioning
confidence: 93%